Patient specific real-time PCR in precision medicine – Validation of IG/TR based MRD assessment in lymphoid leukemia - Schilhabel, Anke; Szczepanowski, Monika; van Gastel-Mol, Ellen J.; Schillalies, Janina; Ray, Jill; Kim, Doris; Nováková, Michaela; Dombrink, Isabel; van der Velden, Vincent H. J.; Boettcher, Sebastian; Brüggemann, Monika; Kneba, Michael; et al. (Frontiers in Oncology, 2023)
Detection of patient- and tumor-specific clonally rearranged immune receptor genes using real-time quantitative (RQ)-PCR is an accepted method in the field of precision medicine for hematologic malignancies. As individual primers are needed for each patient and leukemic clone, establishing performance specifications for the method faces unique challenges. Results for series of diagnostic assays for CLL and ALL patients demonstrate that the analytic performance of the method is not dependent on patients’ disease characteristics. The calibration range is linear between 10-1 and 10-5 for 90% of all assays. The detection limit of the current standardized approach is between 1.8 and 4.8 cells among 100,000 leukocytes. RQ-PCR has about 90% overall agreement to flow cytometry and next generation sequencing as orthogonal methods. Accuracy and precision across different labs, and above and below the clinically applied cutoffs for minimal/measurable residual disease (MRD) demonstrate the robustness of the technique. The here reported comprehensive, IVD-guided analytical validation provides evidence that the personalized diagnostic methodology generates robust, reproducible and specific MRD data when standardized protocols for data generation and evaluation are used. Our approach may also serve as a guiding example of how to accomplish analytical validation of personalized in-house diagnostics under the European IVD Regulation.